(untitled) (Annals of Medical Research, 2021)
Aim: Herpes zoster (HZ) vaccine maintaining routinely aged ≥60 years due to the debated data on long-term effectiveness. We aimed to evaluate age specific incidence of HZ and possible impact of age and gender differences on the onset of disease to contribute age-appropriate vaccination. Materials and Methods: A total of number 599 patients diagnosed with HZ were evaluated retrospectively. Patients were divided into groups by age. Patients’ demographic characteristics, physical examination findings, data of seasonal disease distribution, lesions location, rate of antiviral drug prescription, administered antiviral agent, and presence of accompanying systemic diseases were evaluated. Results: The 599 patients included in this study were 296 (49,4%) male, 308 (50,6%) female and the mean age of total patients was 50.6±18.84 years. There were statistically significant differences between males and females according to the age groups (p=0,006). In addition, the frequency of disease was significantly increased by age (p=0,000). Moreover, HZ incidence peaked in the fifth decade of life and 64,1% of the patients were aged ≥ 45 years. Furthermore, HZ frequency was significantly higher in males (%67.6) than females (%32.4) in aged between 26 to 35 group (p=0,03) and higher in females (%61.7) than males (%38.3) in 46-55 years age group (p=0,012). Conclusion: Sudden menopausal hormone alteration in females between 46 to 55 years of age, may cause an increased frequency of HZ. In this respect, despite current recommendations for vaccinating adults, utilization of HZ vaccine particularly in female patients aged above 45 years may be more beneficial in prevention of disease.